Inventory of Orchid Species in Customary Forest Area of Cipta Karya Village, Sungai Betung District, Bengkayang Regency - Putri Indahsari, Dwi; Linda, Riza; Lovadi, Irwan (Jurnal Biologi Tropis, 2024)
Orchids are one of the flowering plants that have many species and are widely distributed, as well as having different attractions and characteristics in each species and habitat. The aim of this research to inventory the types of orchids in Customary Forest Area of Cipta Karya Village, Bengkayang Regency. The research was conducted using the cruise method. The characteristics observed were the morphology of orchids such as roots, pseudobulbs, stems, leaves, and flowers. The inventory results found 13 species of orchids. Epiphytic orchids were found more commonly in this area, with a total of  9 species, while terrestrial orchids were found with 4 species. The epiphytic orchid species foundware composed of Appendicula sp., Bulbophyllum sp., Coelogyne speciosa, Cymbidium sp., Dendrobium crumenatum, Dendrobium anosmum, Luisia sp., Micropera pallida and Oberonia sp. The terrestrial orchid species found ware composed of Acanthephippium javanicum, Malaxis latifolia, Nephelaphyllum pulchrum, and Spathoglottis plicata.